Chikungunya-Dengue Co-Infection: Reports of Two Cases from Bangladesh - Rahim, Muhammad Abdur; Zaman, Shahana; Uddin, Khwaja Nazim (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Chikungunya and dengue are the two most rapidly spreading mosquito-borne viral infections of global public health concern. Dengue is endemic in Bangladesh and here chikungunya is anemerging infection. Because of the spacio-temporal relationship between chikungunya virus and dengue virus, their co-existence and concurrent outbreaks are not unlikely. Here, we report two cases of chikungunya-dengue co-infections occurring among young Bangladeshi patients. Such co-infectionsneed special attention because pain management of chikungunyamay have adverse implications on patients with concurrent dengue infection. J Bangladesh Coll Phys Surg 2019; 37(2): 86-88